Development of Student Character through the Implementation of Religious Values: An Influential Leadership - Nurkholis, Nurkholis; Santosa, Achadi Budi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
In some Eastern societies, character development is usually inseparable from people's religiosity. This research aims to reveal the role of school principals in creating student religiosity. This research uses a qualitative approach; data collection techniques are carried out through observation, involving oneself in learning activities, and interview techniques with several teachers and school principals. The collected data was validated using triangulation techniques, both sources, and techniques. This research reveals that, through example, the school principal has successfully motivated students to behave religiously. Second, the school has successfully formed students' character by applying ethics, discipline, and care. This research provides implications regarding the importance of the role of example in school principals' leadership to motivate students to behave religiously. This shows that school principals can be solid examples of students practicing religious values.